FLUORINE AND CHLORINE IN MAGMATIC AND METASOMATIC ORE PROCESSES IN THE CU-MO PORPHYRY DEPOSITS OF SIBERIA AND MONGOLIA - Sotnikov V.I.; Berzina A.N.; Berzina A.P.; Ponomarchuk V.A.; Gimon V.O. (My University, 2003)
It was found that F/Cl ratios of biotite and accessory apatite from mineralized porphyry complexes show a distinct correlation with the geochemical type of mineralization in the following deposits: Sora (Cu/Mo = 2-4), 37 and 315, respectively; Zhireken (Cu/Mo = 1), 7.3 and 16; Aksug (Cu/Mo = 40-70), 5 and 11.2; and Erdenetuin-Obo (Cu/Mo = 30-50), 3 and 7.3. An increase in Cu/Mo is accompanied by an increase in fHCl/fHF and XHCl/XHF in metasomatic solutions coexisting with biotite and apatite, respectively, in K-feldspar-bearing metasomatic rocks. An increase in Cu/Mo results also in an increase in fH2O/fHF of solutions at the formation of quartz-sericite metasomatic rocks. An increase in the fluorine content of fluid of molybdenum-rich deposits correlates with the elevated role of igneous rocks with high silica and alkali contents and the intensity of potassium metasomatism in ore-bearing porphyry complexes. There is no correlation between the (87Sr/86Sr)0 value of porphyries and the role of F and Cl.